PERENCANAAN PEMBANGUNAN WORKSHOP & GEDUNG AULA SERBAGUNA SMK NEGERI 4 PARIAMAN BERDASARKAN STANDAR NASIONAL PENDIDIKAN - 2053-2058, Begi Sandi (Universitas Negeri Padang, 2018)
Abstract—. This planning is motivated by the need to plan a workshop and multipurpose building for SMK Negeri 4 Pariaman based on National Education Standard. The planning scheme includes programming, data analysis, concept-making and designing activities. Primary data were obtained from field survey and interview, while secondary data were from literature study and comparative study. Macro analysis techniques were conducted in the form of analysis of the area/site and micro analysis were conducted against the object of planning. There are 2 buildings planned with overall building floor area of 1,540 m², consisting of 2-storey workshop and 1-storey multipurpose building. The spaces needed in the workshop are 1 unit of workshop head office, teacher room, technician room, library, study room, computer room, prayer room, warehouse, and 3 units of toilet. The space needed in the multipurpose building are hall, stage, 2 units of dressing room, 1 unit of control room, 6 units of toilet, and lobby. The building is located on the existing site of SMK Negeri 4 Pariaman. The character of the building is aligned with the character of pre-existing buildings and its function as school buildings. Keywords: Design, Facilities, Space